2010
DOI: 10.1007/s12289-010-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Shape complexity factor for closed die forging

Abstract: The present paper describes the application of a shape complexity factor -a criterion simplify the decision whether a pre-forming step is necessary or not, when a process of closed-die forging is under planning. Direct transformation of the billet into the final shape is possible only when the mass of the forging part is small. In order to produce flawless forging parts, there is a necessity of a proper set of preparatory and pre-forming steps. The forging sequence plays a decisive role for producing flawless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A basic measure used in this context is the Spies ratio S (Spies ), which is calculated by dividing a part's mass m part over the mass of a correctly aligned bounding primitive m primitve , typically a cylinder or a cuboid, made of the same material. Building on this concept, Tomov and Radev () report a selection of shape complexity factors designed to enable the specification of an efficient sequence of forging steps by estimating the work needed for material deformation during the forging process. Similarly, Kerbrat and colleagues () develop a set of manufacturing complexity indices applicable to computer numerically controlled (CNC) machining and AM in order to inform process selection and design modularization approaches for improved manufacturability and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…A basic measure used in this context is the Spies ratio S (Spies ), which is calculated by dividing a part's mass m part over the mass of a correctly aligned bounding primitive m primitve , typically a cylinder or a cuboid, made of the same material. Building on this concept, Tomov and Radev () report a selection of shape complexity factors designed to enable the specification of an efficient sequence of forging steps by estimating the work needed for material deformation during the forging process. Similarly, Kerbrat and colleagues () develop a set of manufacturing complexity indices applicable to computer numerically controlled (CNC) machining and AM in order to inform process selection and design modularization approaches for improved manufacturability and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…Tomov et al [ 22 ] suggested about the consideration of shape complexity factor, especially for the forging of complex‐shaped products. It was observed that the implementation of this factor decreased the amount of work to be done by the forging die.…”
Section: Effect Of Input Parameters On the Forging Process Responsesmentioning
confidence: 99%
“…Significantly fewer publications are devoted to determining the necessity of intermediate or preform steps for hot closed-die forging processes. Criterions for necessity of intermediate steps have been proposed in several studies [18,19,20,21]. The wide range of methods and procedures, both for preform design and necessity of preform steps at hot closed-die forging, demonstrates the importance of the subjects and the absence of a standardized and universal solution to the problem.…”
Section: Introductionmentioning
confidence: 99%